Development of Steel Representation as Embedded Bars in Concrete Using Finite Element Method - Zubaidah A. Al-Bayati; Jassim Jarallah Fahed (Journal of Engineering and Sustainable Development, 2008)
A new model for embedded bar formulation in the finite element analysis is presented, this new model differs from the conventional models, that it can represent the bar in a more accurate way, also it can deal with curved and/or complicated bar geometry. The current formulation is made using finite element analysis by considering the degenerated assumed strain eight-noded shell finite element with each node having five degrees of freedom and nonlinear material properties and solution techniques. The validity of the current formulation is proved by comparing the results obtained from the generated computer program with that of experimentally tested slabs by different researches